VD_FINDINFO Arrêt / 2025 / 744 vom 29. August 2025 - VD Tribunal cantonal (2025)
REMISE DE LA PRESTATION, RESTITUTIONEN GÉNÉRAL, PRINCIPE DE LA BONNE FOI | 25 al. 1 LPGA, 31 al. 1 LPGA, 24 OPC-AVS/AI, 4 al. 1 OPGA